Planta Tropika : Jurnal Agrosains (Journal of Agro Science) Vol.4 No.1 Februari 2016 - Redaksi (Prodi Agroteknologi UMY, 2016)
Planta Tropika : Jurnal Agrosains (Journal of Agro Science) Vol.4 No.1 Februari 2016